The World Health Organization's "National workforce capacity to implement the essential public health functions including a focus on emergency preparedness and response: roadmap for aligning WHO and partner contributions": interpretation and clarification - Kexin SHI; Guangpeng ZHANG; Xiaoyan LI; Yueyun LI; Limin TANG (Editorial Office of Chinese Journal of Public Health, 2023)
Countries are going through tough testing as a result of the recurrent worldwide public health crises in recent years. As a result, boosting public health emergency preparedness and response skills, as well as strengthening public health systems and fundamental functions, has become a hot issue of discussion on a global scale. The World Health Organization (WHO) published " National workforce capacity to implement the essential public health functions including a focus on emergency preparedness and response: roadmap for aligning WHO and partner contributions" (referred to as "roadmap") in May 2022 to assist its member states in strengthening essential public health functions, staffing, and capacity building. In this article, we organize and elaborate on the early basis, vision, aims, and target audience of the WHO roadmap using research methodologies like literature reviews and content analysis. We also offer a thorough explanation of the roadmap's three main action areas, which are to define the functions and services, to deliver competency-based education and to map the occupations. Additionally, the "roadmap" for enhancing public health capacity and developing public health personnel in China was examined by summarizing the experience of public health manpower construction in China.